+0  
 
0
34
1
avatar

Solve this system of equations for x and y in terms of a and b. \

y - 3x = a

x = 2y + 3x + b

 Sep 8, 2021
 #1
avatar+32557 
+1

Multiply the first equation by 2:

 

2y - 6x = 2a      (1)

 

Subtract x and b from both sides of the second equation and rewrite as:

 

2y + 2x = -b      (2)

 

Subtract (1) from (2)

 

8x = -b - 2a   (3)

 

Multiply (2) by 3:

6y + 6x = -3b     (4)

 

Add (1) and (4)

 

8y = 2a - 3b    (5)

 

You can now divide (3) by 8 to get x and (5) by 8 to get y

 Sep 8, 2021

25 Online Users